PERTIMBANGAN HAKIM MENJATUHKAN PUTUSAN TIDAK DAPAT DITERIMA (NIET ONTVANKELIJKE VERKLAARD) DALAM PERKARA WANPRESTASI DI PENGADILAN NEGERI PADANG KELAS 1A (Studi Putusan Perkara No. 92/Pdt.G/2023/PN PDG) - Bambang Hermanto, Abd. Rahmad dan (Normative Jurnal Ilmiah Hukum, 2025)
In the civil law system, a civil lawsuit can be filed by a party who feels aggrieved by an act committed by another party. The lawsuit filed by the plaintiff named Nova Sikma Yenti to the Padang District Court alleges an unlawful act for the defendant's installation of a banner that reads "for sale" on the object of the case, but the Defendant in his exception explained that the legal relationship between the plaintiff and the defendant is a credit legal relationship with the number PK.011/NG//KPR-MG/07-2018 dated July 30, 2018. With a bad credit status, the defendant auctioned the object of the a quo case to return the plaintiff's remaining debt. The research method used in this study is normative juridical, namely an approach carried out by studying laws and regulations. The results of this study indicate that, the Padang District Court Decision in its decision stated that the plaintiff's lawsuit was unacceptable (niet ontvankelijke verklaard) because when the panel of judges conducted a local inspection, a banner was found which was actually admitted to being installed by the plaintiff even though they still argued that the defendant had previously installed the banner. because there is a discrepancy between the plaintiff's argument and what was found by the panel of judges. As emphasized in the Supreme Court Jurisprudence Number: 1112.K/Sip/1967 stating that a claim that is not in accordance with the legal event (rechtfeiten) which should be the basis for the lawsuit, then such a claim must be declared unacceptable"